Morpho-agronomic characterization of Varronia curassavica germplasm conservated “Ex situ” (Bioscience Journal, 2020)
Varronia curassavica Jacq. is a medicinal and aromatic plant native to Brazil. The essential oil of this species is valued by the pharmaceutical industry due to its bioactive substances containing anti-inflammatory properties. This study aimed to morpho-agronomically characterize 27 accessions of the collection of V. curassavica of the Active Germplasm Bank of Medicinal and Aromatic Plants of the Federal University of Sergipe. The experiment consisted of a randomized block design with three replications. The morphological characterization occurred in the field, by evaluating the variables plant height; canopy width; canopy shape; stem diameterstem color; leaf blades width, length, and length/width ratio; leaves, petals, and sepals color. The agronomic characterization was performed using the essential oils extracted from dried leaves by hydrodistillation in a Clevenger apparatus. Leaves dry matter yield per plant and essential oil yield and content were also evaluated. The accessions showed great variation for leaves color, with different shades of green, which allowed separating them into dark green leaf and light green leaf plants. Plant height values ranged from 101.33 cm (VCUR-801) to 345.33 cm (VCUR-701). The clustering analysis of the traits revealed seven distinct groups.  The accessions VCUR-103 and VCUR-001 were the most divergent, whereas the accessions VCUR-401 and VCUR-404 were the most similar. The morpho-agronomic characterization of V. curassavica accessions provides a correct description of the species by pointing out perspectives for genetic improvement, besides optimizing the conservation process.